CURCUMIN, A NATURAL GOLDEN DRUG AND ITS ANTICANCER ASPECTS FROM SYNTHESIS TO DELIVERY: A REVIEW - KRISHNAMURTHY, GEETA; ROY, DEEPTI; KUMAR, JYOTSNA (International Journal of Applied Pharmaceutics, 2020)
Cancer is a dreadful disease and, in most cases, leads to death even when it is being treated. Even though synthetic drugs are still in use for the treatment of cancer, the seriousness of the side effects of these drugs has boggled researcher’s mind to find more effective drugs which will help to overcome the side effects and have greater potency in trying to make the patient completely free of the disease. Recently, researchers turned their attention towards bio-components present in natural products. Curcumin, a polyphenol and the main constituent of a rhizome Curcuma longa, has geared significant interest due to its wide spectrum of therapeutics values, especially anticancer activity. Paper summarizes the chemistry and bio-metabolism of curcumin in the human body. Aim of this review article is to gather the dispersed efforts of researchers predominantly in improving the bioavailability of curcumin. In the present review, comprehensive literature on anticancer activity of Curcumin via combination therapy, structure modification, synthesis of analogues, novel delivery systems have been highlighted. Besides, the review paper explicated several challenges associated with Curcumin as an adjuvant chemotherapeutic agent and emphasizes more on clinical studies.